PENGEMBANGAN VIDEO PEMBELAJARAN SENI RUPA LOKAL: PELUKIS ABDUL KAHAR WAHID - Baso Indra Wijaya Aziz (TANRA: Jurnal Desain Komunikasi Visual Fakultas Seni dan Desain Universitas Negeri Makassar, 2018)
Abdul Kahar Wahid has a name in the field of painting (art) in Indonesia proved with one of his works collected by the National Gallery in Jakarta. In South Sulawesi, he is known as a painter and art educator. It is appropriate that Abdul Kahar Wahid is used as one of the artists who become objects in the subject of Local Arts Studies. The purpose of this research is to complete the video program about Abdul Kahar Wahid that has been made before, by adding comments and testimony from artists and art educators and at the same time validating it. This research is conducted through Research and Development procedure, with field trial. Research development in education is a process for developing and validating educational products including materials and procedures and processes such as; teaching methods, learning management and including learning media. The sample of this study consists of students of Arts Education Studies Program Postgraduate Program of UNM Makassar Batch 2016 consists of 15 people, from students of Art Education Program (S1) 25 people. The results showed that the quality of video display showed a high percentage in both categories and excellent in all fields, such as the readability of text/writing very well (53%.) While the quality of presentation of the material, good and excellent category in all fields, and clarity of purpose learning is very good (53%) and ease of understanding material is good (60%). The product of this research deserves to be used as material and media of art learning especially for the subject of Local Art Study.